The Effect of the PQ4R Learning Model toward Students Reading Comprehension Ability: A Meta-Analysis - Primayana, Kadek Hengki; Dewi, Putu Yulia Angga (STAHN Mpu Kuturan Singaraja, 2023)
This research aims to describe the influence of the PQ4R learning model on students' reading comprehension abilities. This research includes quantitative research, research with a meta-analysis approach, namely calculating the average with effect size. First, formulate the research problem, then proceed to explore relevant research. The research sample is 10 publications. The data analysis technique uses publication bias analysis with trim and fill methods with analysis procedures for calculating effect sizes, heterogeneity tests, forest plot analysis and publication bias analysis. The research results with rank correlation were 0.2046 with p-value (0.417) > (0.05), while the regression method was -0.4942 with p-value (0.621) > (0.05), meaning no publication bias was found.